Pengaruh Motivasi dan Kedisiplinan Belajar terhadap Hasil Belajar Matematika Siswa Kelas VIII SMPN 7 Bukittinggi - Aldes Eka Putri; Aniswita Aniswita (Lembaga Yasin AlSys, 2026)
The effect of learning motivation and learning discipline on mathematics learning outcomes has received attention in various previous studies, but studies that specifically analyze the simultaneous effect of these two variables on eighth-grade students at SMP Negeri 7 Bukittinggi remain limited. This study aims to analyze the effect of learning motivation on mathematics learning outcomes, the effect of learning discipline on mathematics learning outcomes, and the joint effect of learning motivation and learning discipline on students’ mathematics learning outcomes. This study used a quantitative approach with an ex post facto correlational design. The research sample consisted of 51 eighth-grade students selected through simple random sampling from a population of 205 students. Data were collected using a learning motivation questionnaire, a learning discipline questionnaire, and a mathematics learning outcomes test, and were then analyzed using simple linear regression and multiple linear regression with the assistance of IBM SPSS Statistics. The results showed that learning motivation had a positive and significant effect on mathematics learning outcomes, with a contribution of 33.089%; learning discipline had a positive and significant effect, with a contribution of 32.2044%; and learning motivation and learning discipline simultaneously had a positive and significant effect on mathematics learning outcomes, with a contribution of 47.21%. These findings contribute to the development of studies in mathematics education, particularly regarding the role of students’ internal factors in improving learning outcomes. The conclusion of this study affirms that learning motivation and learning discipline are important factors in supporting the success of mathematics learning. The implications of this study include theoretical contributions to the development of educational literature and practical implications for teachers and schools in designing learning strategies that can enhance students’ learning motivation and learning discipline.